Disaster Preparedness and Climate Change in Cuba: Management and Adaptation - Kirk, Emily J.; Story, Isabel; Clayfield, Anna (Lexington Books, 2021)
As a result of climate change, ocean temperatures are warming and sea levels are rising. Natural disasters have been increasing in frequency and ferocity. Yet, over six decades, Cuba has developed a world-leading model for disaster preparedness and risk reduction. Disaster Preparedness and Climate Change in Cuba: Management and Adaptation discusses the island’s ongoing resilience against the impacts of climate change. Its commitment to disaster preparedness and management are lauded by international bodies, such as the United Nations and World Health Organization, and by governments from across the globe. Comprised of research from leading scholars, policy makers, and activists, this comprehensive, multidisciplinary analysis of Cuba’s model explores why Cuba’s approach to emergency disaster response is such a success and the aspects that make it so distinct, while also informing readers about the much-needed improvement of international approaches and policies. Scholars of communication, environmental studies, and Latin American studies will find this book particularly interesting.